ECCAS's Infrastructure : A Regional Perspective - Ranganathan, Rupa; Foster, Vivien (2012)
Sound infrastructure is fundamental for growth across the Economic Community of Central African States (ECCAS). During 1995-2005, improvements in infrastructure boosted growth in Central Africa by 1 percentage point per capita annually, primarily due to the introduction and expansion of mobile telephony. Improved roads also made a small contribution. Conversely, inadequate power deterred growth to a greater degree than elsewhere in Africa. ECCAS must address a complex set of challenges. Economic activity takes place in isolated pockets separated by vast distances. Two countries are landlocked and dependent on regional corridors; seven countries have populations of under 10 million; and eight have economies that are smaller than $10 billion/year. This difficult economic geography demands a regional approach to developing infrastructure. Yet Central Africa's infrastructure has the poorest performance record in all of Africa on most aggregate indicators. Transportation is slow and the most expensive in Sub-Saharan Africa, with poor road conditions, border delays, port delays, time-consuming administrative processes, no integrated railway network, and inefficient air transport. The ICT backbone is still in its early stages; access rates are low and the prices of critical services are the highest in Africa. ECCAS has the least-developed power sector on the continent despite significant hydropower resources. If Central Africa's infrastructure could be improved to the level of Mauritius, regional growth performance would be boosted by some 5 percentage points, with power making the strongest contribution. The cost of such an improvement is estimated at $1.8 billion/year for a decade and will require external assistance.